Visual Inspection of Acetic Acid (VIA) to Detect PreCancerous Cervical Cancer in Rural Areas of Sarawak - Mardiana, Kipli; Abigail Rembui, Jerip; Awi, Idi; Yee, Y. K.; Soe, L.; Myat, San Yi; Mi, M. K.; Thidar, S.; Harris, N, S. (Malaysian Medical Associatio, 2019)
Introduction: Cervical cancer is still the leading cause of gynaecological cancer in Sarawak. Low awareness on cervical screening and logistic problems are the main reasons for delay in diagnosis, especially in rural areas. Although pap smear screening had been implemented for decades, failure to get early treatment and frequent defaulters are factors that need to be tackled for rural women. Objectives: The Sarawak Travelling Women Health Project is aimed to improve pre-cancerous cervical cancer detection in rural areas using the Visual Inspection of Acetic Acid (VIA) method. This project also helps to shorten the duration of follow up and treatment for patients with pre-cancerous lesion of cervix. Methods: Cervical screening campaigns outside Kuching areas were conducted from June until December 2018 by the Obstetrics and Gynaecology Department of Universiti Malaysia Sarawak (UNIMAS) in collaboration with Pink and Teal Empower, a Non-Government Organization. VIA was performed for all women below 50 years old. Patients with positive VIA were a colposcopy appointment and cervical biopsies are taken at the clinic. Results: During the campaign period, 83 out of 333 women were found to be VIA positive, but only 47 women turned up for the colposcopy. This high number of defaulters is mostly due to logistic reasons. Two cervical biopsies were confirmed as Cervical Intraepithelial Neoplasia (CIN) 2, 15 cases with CIN 1, one case of microglandular hyperplasia while 19 biopsies turned out to be cervicitis. The pickup rate for CIN during the outreach was about 20.4%. Conclusion: VIA is useful in low resource area with difficult access to tertiary centres as it enables faster diagnosis for CIN. However, proper training is needed to avoid false positive results and unnecessary intervention. To reduce the rate of defaulters, cervical biopsy for VIA positive women should be done in the field during the same setting.